Letter to Editor COVID-19 outbreak and medical waste: Challenge in hand - Hassan Musa; Taha H. Musa; Idriss H. Musa; Olayinka Oderinde (Intelektual Pustaka Media Utama, 2020)
The ongoing pandemic of novel coronavirus disease, COVID19, which first reported in Wuhan, China, inDecember 2019, [1] and caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV2) has resulted to more than 6,881,352 confirmed cases in the world, and 399,895 global deaths, as reported in 8:36am CEST, 8 June 2020. [2] It has been reported that the primary spread of COVID-19 via human transmission is during close contact, most often through small droplets spread by coughing, sneezing, and talking. [3] Researchers and health experts have discovered that wearing of appropriate face masks can significantly reduce the transmission up to the 75%.